2020
DOI: 10.3390/ijerph17020485
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Age and Gender in Perceived Vulnerability to Infectious Diseases

Abstract: Background: The study of the immune system has been approached using two separate paths, the biological immune system and the behavioral immune system. Recently, Gangestad and Grebe proposed a unique integrated compensatory immune system, where both systems work together and one of them could compensate for the other when necessary. However, few studies have confirmed the existence of this integrated compensatory immune system. Our study represents an attempt to explore the existence of this unique immune syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 40 publications
6
28
0
2
Order By: Relevance
“…While the females in this study had slightly higher scores in perceived infectability and germ aversion than the males, there were no statistically significant differences. A study 21 on perceived vulnerability to disease provided support to the notion that the women had a higher score than the men. Moreover, previous reports have shown that sex-based differences exist concerning the ability to cope with stress.…”
Section: Discussionmentioning
confidence: 93%
“…While the females in this study had slightly higher scores in perceived infectability and germ aversion than the males, there were no statistically significant differences. A study 21 on perceived vulnerability to disease provided support to the notion that the women had a higher score than the men. Moreover, previous reports have shown that sex-based differences exist concerning the ability to cope with stress.…”
Section: Discussionmentioning
confidence: 93%
“…Gender differences are only significant in younger participants, with women scoring higher on perceived vulnerability than men. 16 Women's greater perceived vulnerability to disease may be based on the history of developmental psychology and on current exposure to disease threat. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that pathogen disgust sensitivity is negatively related with hand-grip strength, a simple measure of an individual's general health [12]. Furthermore, disgust sensitivity has been shown to increase with age when the immune system weakens [13].…”
Section: Introductionmentioning
confidence: 99%